Qualitative Analysis of Symptoms from the Central Thalamic Deep Brain Stimulation Trial for Traumatic Brain Injury. - Gerber, Linda M; Shulman, Kaiulani S; Wright, Megan S; Schiff, Nicholas D; Fins, Joseph J (NeuroRehabilitation, 2025)
Background: Studies of moderate-to-severe traumatic brain injury (TBI) report persistent clinical impairment post-injury. In the CENTURY-S study of deep brain stimulation (DBS) in chronic TBI, Schiff et al.'s paper, "Thalamic deep brain stimulation in traumatic brain injury: a phase 1, randomized feasibility study" demonstrated improvements in executive control. A companion narrative analysis by Fins et al., "Subject and Family Perspectives from the Central Thalamic Deep Brain Stimulation Trial for Traumatic Brain Injury" Parts I and II described improvements in cognitive, behavioral, and emotional capabilities. Objective: The present study provides an aggregate symptom assessment utilizing pre- and post-DBS narratives from subjects and their family members. Methods: Drawing upon participants from the CENTURY-S study, Fins et al. conducted semi-structured interviews with five subjects with moderate-to-severe TBI and their family members. Transcripts were subsequently coded deductively and inductively in Dedoose by two independent investigators. Results: Subjects and families frequently volunteered memory and cognitive symptoms as well as difficulties with self-regulation, frustration, and irritability pre-DBS. Following stimulation, four subjects and four families noted improvement in memory and attention and focus, while three subjects and five families volunteered improvements in self-regulation. Fatigue improved in three subjects who previously reported this symptom and in one who did not. Conclusions: Secondary qualitative analysis of narrative data of DBS trial participants supports the incorporation of qualitative data as additional outcome measures in studies of DBS in TBI.